Collaborative Leadership Is Key for Maine’s Forest Products Industry - MacDonald, Brooke; Horne, Lydia; De Urioste-Stone, Sandra; Haskell, Jane; Weiskittel, Aaron (Maine Policy Review, 2018)
The forest products industry is economically, socially, culturally, and environmentally important to Maine. Thus, Maine’s future economy depends greatly on the leadership in this industry. Effective leadership grows out of understanding the changes that are taking place in the industry and finding innovative ways to address unexpected challenges and emerging opportunities. During times of change, many industry leaders settle for maintaining the status quo. The forest products industry in Maine, however, is systematically assessing the ways the landscape is changing. Rather than continuing on the same path, the industry is gathering insights that could lead to a vibrant, but perhaps different, future. What we report here is an innovative process that actively solicits insights reflecting the diverse perspectives of those who work in different subsectors of the industry. What is emerging is evidence of the importance of collective leadership that brings together different areas of knowledge. We report on the process, the emerging findings, and the implications for leadership in moving forward.